Tradition and Technology: The Adaptation of Social Reciprocity in Digital Invitations in Sindangagung Village, Kuningan Regency, West Java - Muhammad Ihsan Aulia Rahman; Lestari, Soetji; Sutoyo, Ignatius Suksmadi (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
This study aims to analyze Generation Z’s perspective in interpreting reciprocity within the Kuningan kondangan tradition in the digital era. This phenomenon is significant to examine following the emergence of digital invitations, which have transformed conventional patterns within the Kuningan kondangan tradition. These changes have created new dynamics in the way Generation Z maintains reciprocal relationships. The theoretical framework used to analyze the findings is the theory of the gift proposed by Marcel Mauss. This research employs a qualitative approach with a descriptive method. Data were collected through non-participant observation, semi-structured interviews, and documentation. Informants were selected using the snowball sampling method, beginning with one member of Generation Z involved in reciprocal practices within the kondangan tradition, with the criterion of having experienced both giving and receiving in the tradition. The initial informant then recommended other participants, gradually forming a network of respondents. Data analysis was conducted using the analytical framework of Miles, Huberman, and Saldaña. The findings indicate that digital invitations have become increasingly widespread, particularly among Generation Z. The emergence of digital invitations has transformed patterns of reciprocity in the Kuningan kondangan tradition, making them more investment-oriented and transactional in nature.